La pericolosità sociale e i mass media - Tulli, Federico (Il sogno della farfalla, 2019)
This article analyzes how inappropriate terminology adopted by mass media can alter the accuracy in reporting crimes, thus determining a false perception of the facts by the public opinion. The examples mentioned by the author particularly focus on the meaning of some recurrent words used in the title and description of crime news.